Site‐selective immobilization of anti‐CD34 antibodies to poly(l‐lactide) for endovascular implant surfaces. Issue 2 (2nd September 2013) - Petersen, Svea; Strohbach, Anne; Busch, Raila; Felix, Stephan B.; Schmitz, Klaus‐Peter; Sternberg, Katrin
Abstract Aiming at a speed up of the re‐endothelialization process of biodegradable endovascular implants, novel approaches for the functionalization of poly(l‐lactide) (PLLA) with anti‐CD34 antibodies were established. We propose a three‐step process involving PLLA surface activation with functional amino groups, attachment of a protein repelling peptide spacer, and covalent random or site‐selective immobilization of the antibodies. Obtainable antibody surface densities and antigen binding capacities were thoroughly evaluated by means of enzyme‐linked immunosorbent assay. Results indicate that a lower amount of anchoring sites on the antibody favors high coupling efficiency, while localization of the anchoring sites, facing the antigen binding moiety, strongly enhances the antigen capture capacity of the support. Besides minimization of physisorption and cell adhesion exemplarily shown with bovine serum albumin, avidin, and human umbilical vein endothelial cells, respectively, the inclusion of the protein‐repelling spacer strengthened this effect, yielding antigen capture capacities exceeding values so far reported in literature. In contrast, the number of amino groups on the PLLA surfaces, which is indeed highly dependent on the applied activation procedure, does not seem to influence antibody coupling efficiency and antigen capture capacity considerably. This allows the choice of surface activation treatment, plasma or wet‐chemical, regarding other processing parameters as for instance sterilizability or favored modification depth. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 345–355, 2014.